(untitled) (Journal of Renal and Hepatic Disorders, 2021)
A gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract. It is caused by the mutation in KIT and PDGFRα genes. It constitutes <1% of all gastrointestinal tumors. Duodenal GISTs constitute 4.5% of all GISTs. We report a 61-year-old lady, presented with generalized abdominal pain, vomiting, abdominal distension, and nausea for the last 3 years. Physical examination showed a pallor and on abdominal examination, a large palpable mass was extending from the pelvis to the right upper quadrant of the abdomen. The CT scan showed a large heterogeneously echogenic mass in the abdomen and pelvis with no lymphadenopathy and distant metastasis in this region. Laparotomy showed a large globular mass extending from the pelvis to the right upper quadrant of the abdomen adherent to the wall of a third part of the duodenum. Complete surgical resection of tumor done with an intact capsule. Microscopic examination showed neoplastic spindle cells with tumor necrosis. An immunohistochemical study confirmed GIST.